2014
DOI: 10.1017/s1751731114000445
|View full text |Cite
|
Sign up to set email alerts
|

Effects of neonatal surgical castration and immunocastration in male pigs on blood T lymphocytes and health markers

Abstract: Surgical castration in pig husbandry is criticized for welfare reasons. Thus, it is necessary to evaluate alternative ways of rearing male pigs, such as entire or immunocastrated animals. Immunocastration is a vaccination directed against gonadotropin-releasing hormone (GnRH) to suppress the production of sexual hormones. This study aimed at investigating the effects of these two methods of castration in comparison with intact male pigs on blood T-lymphocyte subsets and function, the immunoglobulin (Ig) respon… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
3
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 27 publications
0
3
0
Order By: Relevance
“…However, these sex-based differences were not observed in Iberian pigs, with the exception of ADA enzyme that appeared higher in males in the finishing stage. This lack of sex differentiation on the levels of markers could be related to the castration of male Iberian pigs that could have caused a low androgenic influence on the immune system and a less aggressive behavior (46). The higher ADA values observed in male finishing Iberian pigs in comparison to females could have been influenced by other factors that should be further studied, since no explanation could be established with the actual data.…”
Section: Discussionmentioning
confidence: 99%
“…However, these sex-based differences were not observed in Iberian pigs, with the exception of ADA enzyme that appeared higher in males in the finishing stage. This lack of sex differentiation on the levels of markers could be related to the castration of male Iberian pigs that could have caused a low androgenic influence on the immune system and a less aggressive behavior (46). The higher ADA values observed in male finishing Iberian pigs in comparison to females could have been influenced by other factors that should be further studied, since no explanation could be established with the actual data.…”
Section: Discussionmentioning
confidence: 99%
“…However, studies in male mice confirm blood lymphocyte subsets showed a decreasing trend after GnRH agonist administration in pre-pubertal males, while no differences were observed in post-pubertal males (31). Immunization against GnRH didn't alter the percentages of CD3+, CD3+CD4+ and CD3+CD8+ lymphocytes in male pigs (53), wheares, increased the number of CD3+ and CD4+ T lymphocytes initially in the peripheral blood, and eventually restored the T lymphocytes to normal levels in rats (37). GnRH antagonist treatment decreased the percentage of CD4+CD25+ cells, reduced mitogen-induced CD8 T cells IFN-g expression, but didn't affected the ratio of CD4 to CD8 T cells in adult males (32).…”
Section: Discussionmentioning
confidence: 88%
“…However, this procedure in the swine species is still recurrent is some countries, such as Brazil, due to the androsterone, a steroid produced in the animal's testicles during sexual maturity, which exhales an unpleasant smell during the cooking of the meat which causes rejection of the meat by the consumers (Iocca et al, 2015). In this context, studies are necessary for the development of viable alternatives to the conventional surgical castration of male piglets, still practiced in the majority of swine farms in Brazil and, largely, without the use of anesthetic drugs (Leclercq et al, 2014).…”
mentioning
confidence: 99%